Clinical value of entire-circumferential intraoperative frozen section analysis for the complete resection of superficial squamous cell carcinoma of the tongue. (December 2021) - Asoda, Seiji; Miyashita, Hidetaka; Soma, Tomoya; Munakata, Kanako; Yamada, Yuka; Yasui, Yuta; Kudo, Yoko; Usuda, Shin; Hasegawa, Toshihiro; Nakagawa, Taneaki; Kawana, Hiromasa
Highlights: Entire-circumferential intraoperative frozen section analysis (e-IFSA) was assessed. e-IFSA showed 99.3% accuracy in resection of superficial tongue carcinoma. Iodine staining with an e-IFSA resulted in a complete resection rate of 100%. An e-IFSA may improve treatment accuracy, irrespective of the surgeon's experience. Since the 5-year LC and OS rates were 100%, an e-IFSA may lead to a good prognosis. Abstract: Objectives: We aimed to evaluate the clinical value of an entire-circumferential intraoperative frozen section analysis (e-IFSA) for the complete resection of superficial squamous cell carcinoma (SCC) of the tongue. Materials and Methods: A total 276 specimens from 51 patients with pT1-2, N0, mucosal or submucosal invasion SCC were analyzed to evaluate the diagnostic accuracy of the e-IFSA and the added value of the e-IFSA to iodine staining. The e-IFSA results were compared with the final histologic results obtained using permanent sections. All specimens for the e-IFSA were taken over the entire circumference 5 mm outside from the iodine unstained areas. The outline of the main resected specimen after taking these outer mucosal specimens were defined as the surgical margins determined by iodine staining alone. Results: The e-IFSA results were in excellent agreement with final histological results (Cohen's kappa value: 0.85) and the e-IFSA showed high sensitivity (100%) and high negative predictive value (100%). The actual complete resection rate with an e-IFSA was 100% (51/51), and no patient required additional resection after surgery. In contrast, 10/51 patients (20%) patients showed residual atypical mucosal epithelium at or beyond the margin determined by iodine staining alone; this difference was statistically significant (P = 0.002). The 5-year local control rate and 5-year overall survival rate after this procedure were both 100%. Conclusion: An e-IFSA has additional value when performed in conjunction with iodine staining. An e-IFSA would be useful for achieving complete resection of superficial SCC of the tongue.